Methodological issues of education system development in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Methodological issues of education system in the light of conducted reforms in Kazakhstan are considered. The evaluation of conducted mea sures of the Ministry of Education and Science of the Republic of Kazakh stan and their conformity with expected results are given. The succession of perspective activities, which are adequate to established situation and which allow to speed up the complex development of country’s education system in accordance with new challenges is suggested.
Keywords: pedagogical problems; multilevel continuous education; selfeducation and selfdevelopment; standards and strategic priorities of education development; measures and mechanisms of education system regulation.